Gambaran Kejadian Ikutan Pasca Imunisasi Covid-19 pada Mahasiswa Fakultas Kedokteran UKI Penyintas Covid-19 dan Non Penyintas Covid-19 - Desy Ria Simanjuntak; Jendri Mamangkey; Nive Winda Sari Lumban Tungkup; Anggi Izdihar Mahaswari; Talitha Amalia; Bethaniel Roy Matthew (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Adverse Events Following Immunization (AEFI) is defined as 'any adverse medical event that occurs after immunization, but which does not necessarily have a cause-and-effect relationship with vaccine use. Research conducted by krammer, et al said that vaccine recipients with pre-existing immunity (seropositive) experienced systemic side effects with a much higher frequency than antibody-nave vaccines. UKI Medical Faculty student environment class 2018 and 2019. The research design used is descriptive research with a sample of primary data taken using google form as a media for filling out questionnaires with a sampling method with simple random sampling , then the data is collected and will be processed with the Microsoft program excel. The number of respondents in this study amounted to 229 respondents, consisting of 115 students of class 2018 and 114 students of class 2019. The percentage of students who were non-survivors of COVID-19 was 77.73% and survivors of COVID-19 was 27.73%. Types of vaccines 1,2, and 3 received by the two groups included Sinovac, Astrazeneca, Moderna, and Pfizer. Symptoms of AEFI in non-survivors of COVID-19 are dominated by local symptoms in the form of pain at the injection site (vaccine 1; 88.3%, vaccine 2: 92.6%, vaccine 3: 93.8%), followed by other systemic symptoms such as myalgia., fever, and headache (vaccine 1: 11.7%, vaccine 2: 7.4%, vaccine 3: 6.2%). Symptoms of AEFI in COVID-19 survivors are dominated by local symptoms in the form of pain at the injection site (vaccine 1; 69.05%, vaccine 2: 93.55%, in vaccines 3 respondents experienced mixed local and systemic symptoms. Adverse Event Following Immunization (AEFI) which dominated in both groups in the form of local symptoms such as pain at the injection site, followed by systemic symptoms such as fever, myalgia, and headache Keywords: COVID-19, COVID-19 Vaccine, Adverse Events Following Immunization (AEFI)